Quantitative and Qualitative Measurement of K- Means and Fuzzy C Means, the Detection and Extraction of MRI Cerebellum lesions - G, Prathibha; Mohana, Dr. H.S (International journal of recent technology and engineering, 2019)
Clustering is an unaided examination with two totally various procedures: hard clustering and soft clustering. K-Means might be a hard clustering procedure and FCM might be a soft clustering procedure. In this paper, a performance live is administrated on these two algorithms to search out the higher one for detection and extraction of cerebellum lesion in MRI. Each subjective and objective evaluations are administrated. Varied applied mathematical measures like MSE, PSNR, ROI, NROI, Compression ratio, accuracy are utilized for target investigation of the consequences of the near examination of the two calculations. Abstract investigation is administrated by subject specialists. From this examination, it is discovered that FCM is delivering higher quality segmentation results than K-Means regarding accuracy and ROI segregation. Then again, K-Means is overpowering the relatively lesser measure of time for image segmentation than FCM. In this way, on the off chance that accuracy is given parcel of need than time complexness, at that point FCM should be an essential inclination.